Sesame Street. Wonderful world of friends! [videorecording (DVD)]. - Stefani, Gwen, 1969-; Santos, Romeo, 1981-; Groban, Josh; Legend, John (Sesame Street., 2021)
Celebrate friendship with Sesame Street! Join Elmo, Big Bird, Rosita, and their friends to learn about music, food, and more from around the world. With songs and segments from the show, kids will learn dance moves, celebrate other cultures' holidays and traditions, and meet international visitors on Sesame Street. Big Bird is excited to meet his pen pal from India, Telly and Zoe help Leela celebrate the Indian holiday Rakhi, and Rosita shares what being Mexican means to her.